Recent strategic planning decisions by the University of Alberta and their implications for its faculty of extension - Dennis Haughey (Adult Education Research Conference, 1995)
The purpose of this paper is to examine the implications of recent strategic planning decisions by the central administration of the University for the vitality of its Faculty of Extension and the institution’s extension function in general.